Infectious Disease Traveler Mobile Application Based on Need Assessment Analysis in Malaysian Students - Farindira Vesti Rahmasari; Wulan Noviani; Cahya Damarjati; Titih Huriah; Ferika Indarwati; Umniyyah Agsanie; Tesaviani Kusumastiwi; Mallika Imwong; Chong Mei Chan (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Major risks to world health are posed by infectious illnesses such as leptospirosis, hepatitis, malaria, dengue, and tuberculosis. Many diverse measures have been taken to fight infectious disease. However, cases persist despite these efforts, emphasizing the necessity for creative methods of managing and preventing disease. As it integrates mobile health (mHealth) solutions, the research can potentially revolutionize travel medicine. It is vital to give easily accessible and trustworthy health information that can lower the risks of infectious disease while traveling, as the number of students and the general public who travel is increasing. It was qualitative research. Qualitative study explores the potential of mobile health (mHealth) solutions to enhance travel medicine by providing accessible and reliable information to mitigate infectious disease risks among travelers. There 39 informants for the research. The inclusion criteria includes persons with a history of traveling or plans to travel. The data was collected by using questionnaire, FGD, and in-depth interviews for qualitative analysis. Findings from 39 informants, collected through questionnaires, focus group discussions, and in-depth interviews, highlight the need for innovative, user-friendly applications to improve the quality and efficiency of health information for travel-related disease prevention and management. By incorporating mHealth solutions, travelers may receive higher-quality, more useful, and more efficient health information that may be used to manage travel-related health concerns.